Pendekatan Arsitektur Neo-Vernacular Dalam Perancangan Creative Hub Untuk Aktivitas Masyarakat Di Kabupaten Manggarai Barat - Aristo J. Songko; Endang Setyawai (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
West Manggarai Regency of East Nusa Tenggara province became one of the backbones of the national tourism sector when its capital city, Labuan Bajo, was selected as one of the ten priority tourism destinations in 2016. Tourism development is improved as a sector that promises to bring in large revenues for the country, especially in areas with abundant natural and cultural resources. On the other hand, the regent of West Manggarai continues to race in order not to waste the golden opportunities. One thing the local government continues to strive for is that regional tourism dynamics can impact economic development and growth, as well as improve the welfare of local communities in the creative product sector, the directorate of the creative music industry, and the performing arts. The neo-vernacular architectural approach is used in the design of a creative hub, with a descriptive analysis method that uses qualitative research by collecting and recording detailed data on various problems related to the design object. The results of the application of neo-vernacular architecture are in the form of facades, roof shapes, materials, and spatial zoning. Later, this creative hub is expected to open up jobs for creative actors, become a place to preserve and develop Manggarai culture, and become a new tourist destination in the Labuan Bajo city.